Predation Stress Causes Excessive Aggression in Female Mice with Partial Genetic Inactivation of Tryptophan Hydroxylase-2: Evidence for Altered Myelination-Related Processes - Evgeniy Svirin; Ekaterina Veniaminova; João Pedro Costa-Nunes; Anna Gorlova; Aleksei Umriukhin; Allan V. Kalueff; Andrey Proshin; Daniel C. Anthony; Andrey Nedorubov; Anna Chung Kwan Tse; Susanne Walitza; Lee Wei Lim; et al. (Cells, 2022)
The interaction between brain serotonin (5-HT) deficiency and environmental adversity may predispose females to excessive aggression. Specifically, complete inactivation of the gene encoding tryptophan hydroxylase-2 (Tph2) results in the absence of neuronal 5-HT synthesis and excessive aggressiveness in both male and female null mutant (Tph2−/−) mice. In heterozygous male mice (Tph2+/−), there is a moderate reduction in brain 5-HT levels, and when they are exposed to stress, they exhibit increased aggression. Here, we exposed female Tph2+/− mice to a five-day rat predation stress paradigm and assessed their emotionality and social interaction/aggression-like behaviors. Tph2+/− females exhibited excessive aggression and increased dominant behavior. Stressed mutants displayed altered gene expression of the 5-HT receptors Htr1a and Htr2a, glycogen synthase kinase-3 β (GSK-3β), and c-fos as well as myelination-related transcripts in the prefrontal cortex: myelin basic protein (Mbp), proteolipid protein 1 (Plp1), myelin-associated glycoprotein (Mag), and myelin oligodendrocyte glycoprotein (Mog). The expression of the plasticity markers synaptophysin (Syp) and cAMP response element binding protein (Creb), but not AMPA receptor subunit A2 (GluA2), were affected by genotype. Moreover, in a separate experiment, naïve female Tph2+/− mice showed signs of enhanced stress resilience in the modified swim test with repeated swimming sessions. Taken together, the combination of a moderate reduction in brain 5-HT with environmental challenges results in behavioral changes in female mice that resemble the aggression-related behavior and resilience seen in stressed male mutants; additionally, the combination is comparable to the phenotype of null mutants lacking neuronal 5-HT. Changes in myelination-associated processes are suspected to underpin the molecular mechanisms leading to aggressive behavior.